Impact of self-evaluation strategy on mathematical achievement: An empirical study among undergraduate mathematics education students - Oguguo, Basil Chinecherem; Ugorji, Clifford O.; Ohwoavworhua, Loveth (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Given Nigerian students’ poor achievement in mathematics performance over the years, researchers are exploring how a self-evaluation learning strategy can improve this situation. This strategy empowers students to assess their own understanding of learning materials in the subject, apply concepts effectively, and accurately complete tasks.Aim: The author examined the impact of self-evaluation strategy on mathematical achievement among undergraduate mathematics education students in Nigeria.Method: The researcher adopted Correlational survey research design. Participants (N = 357) were 3rd year undergraduate mathematics students at a public University in Nigeria. Data was collected using two researcher-developed instruments: Students’ Self-evaluation Learning Strategy Questionnaire (SSLSQ) and Students Mathematics Academic Achievement Proforma (SMAAP). The internal consistency reliability index obtained using Cronbach Alpha was 0.77. Data collected were analyzed using simple linear regression analyses through SPSS version 26.0 as well as regression analysis through Process model 1 procedure IBM SPSS version 4.00.Result: Findings from the study revealed that self-evaluation learning strategy positively impacted students' achievement in Mathematics. Specifically, 22% of the variation in students’ achievement in Mathematics is attributed to self-evaluation learning. The stdy also revealed a significant difference in the mean achievement score of mathematics students taught in public universities who used self-evaluation compared to those who did not.Conclusion: Students should be encouraged by Mathematics teachers to adopt Self-evaluation strategy when assessing their learning outcomes to enhance their learning of the subject.